Article RETRACTED due to manipulation by the authors Football coach's strategy in preventing aggressive behavior in adolescents - Nawan Primasoni; Sulistiyono Sulistiyono; Fatkurahman Arjuna; Abdul Aziz Purnomo Shidiq; Nurul Zuriah; Sabariah Sabariah; Rufi’i Rufi’i; Harmanto Harmanto; Ridho Bahtra; Syaifullah Yophi Ardiyanto; Safrudin Safrudin; Ratko Pavlovic (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to review the types of strategies that football coaches employ to prevent aggressive behavior in adolescents. Using the systematic literature review, data were obtained from articles searched through Google Scholar. The search focused on those published in Scopus-indexed journals published between 2019 and 2024. The keywords involved "Strategy And Soccer Coaches And Prevention And Aggressive Behavior And Teenagers". The search generated 15,400 articles as initial results. To be included in the review, inclusion and exclusion criteria were applied. The articles were screened again using these criteria, and 19 articles that fit the theme and met the inclusion requirements were yielded. The process of the article selection in this study followed the PRISMA guidelines. The main findings of this study emphasized several factors that play a key role in creating a supportive environment for young athletes. The first factor was emotional education. Teaching athletes to recognize and manage their emotions helped football coaches reduce athletes’ aggressive reactions, especially during the pressure of competition. In addition, open and consistent communication between soccer coaches and athletes was reported to reinforce positive interpersonal relationships, which in turn lowered levels of aggressiveness on the field. Finally, building a team culture that emphasizes the values of cooperation and mutual respect has also been proven effective in preventing aggressive behavior. Therefore, soccer coaches have a great responsibility not only to develop athletes' technical skills but also to shape their character through an integrative and sustainable approach.